2011
DOI: 10.1242/dev.061762
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lung endoderm progenitor cell behavior by miR302/367

Abstract: SUMMARYThe temporal and spatial control of organ-specific endoderm progenitor development is poorly understood. miRNAs affect cell function by regulating programmatic changes in protein expression levels. We show that the miR302/367 cluster is a target of the transcription factor Gata6 in mouse lung endoderm and regulates multiple aspects of early lung endoderm progenitor development. miR302/367 is expressed at early stages of lung development, but its levels decline rapidly as development proceeds. Gain-and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 51 publications
(52 reference statements)
2
81
0
1
Order By: Relevance
“…After a 30-min pulse of BrdU, we determined the percentage of proximal (Ecad+, Sox2+) and distal (Ecad+, Sox2−) proliferation in the epithelium of control and Sox9 LOF lungs at E14.5. As previously demonstrated (1,(6)(7)(8)(9)(10)(11)14), we confirmed that distal epithelial proliferation was significantly higher than proximal epithelial proliferation in control tissue (40.2% ± 1.7% vs. 29.6% ± 1.7%; P < 0.0005; n = 12) (Fig. 2B and SI Appendix, Fig.…”
Section: Epithelial-specific Loss and Gain Of Sox9 Causes Severe Bransupporting
confidence: 88%
See 1 more Smart Citation
“…After a 30-min pulse of BrdU, we determined the percentage of proximal (Ecad+, Sox2+) and distal (Ecad+, Sox2−) proliferation in the epithelium of control and Sox9 LOF lungs at E14.5. As previously demonstrated (1,(6)(7)(8)(9)(10)(11)14), we confirmed that distal epithelial proliferation was significantly higher than proximal epithelial proliferation in control tissue (40.2% ± 1.7% vs. 29.6% ± 1.7%; P < 0.0005; n = 12) (Fig. 2B and SI Appendix, Fig.…”
Section: Epithelial-specific Loss and Gain Of Sox9 Causes Severe Bransupporting
confidence: 88%
“…These saccules will eventually give rise to mature alveoli in the adult mouse (2)(3)(4)(5). Several signaling pathways and transcription factors are known to play roles in branching morphogenesis; however, mechanisms controlling morphogenetic movements in the lungs have only recently started to gain attention (1,(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…These include members of the miR-17-92 cluster (25) and the miR302/367 cluster (26). Overexpression of the miR-17-92 cluster promotes cell proliferation and inhibits lung epithelial progenitor cell differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of the miR-17-92 cluster promotes cell proliferation and inhibits lung epithelial progenitor cell differentiation. GATA6, a key transcription factor for formation of mature alveoli, transcriptionally regulates the miR-302/367 cluster (26). Transgenic mice with no expression of this miRNA cluster had smaller lungs prenatally and displayed reduced cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Some key advances aimed at overcoming these safety concerns have been achieved for the production of iPS cells [11,12,68], and these may be applicable to iTD. Such advances include using nonintegrating viruses (such as adenovirus or episomal plasmid transfection) [69][70][71], treatment of cells with cell-penetrating recombinant reprogramming factor proteins [72], transposon-based systems [73] and the delivery of reprogramming factors in plasmids [74][75][76], repeated transfection of modified mRNA encoding reprogramming factors [77], and miRNAs [78,79].…”
Section: Safety Concerns Of Transdifferentiated Cellsmentioning
confidence: 99%